2019
DOI: 10.1039/c9cp04832d
|View full text |Cite
|
Sign up to set email alerts
|

Free volume, gas permeation, and proton conductivity in MIL-101-SO3H/Nafion composite membranes

Abstract: The influence of free volume size on the gas permeability of MIL-101-SO3H/Nafion composite membranes is closely related to the size of the particular gas molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 90 publications
3
9
0
Order By: Relevance
“…These facts explain why the significant increase of I 2 and remarkable decrease of I 3 and I 4 are detected. A similar inhibition effect was also observed in Nafion 19–22 and other graft‐type sulfonated membranes 23 …”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…These facts explain why the significant increase of I 2 and remarkable decrease of I 3 and I 4 are detected. A similar inhibition effect was also observed in Nafion 19–22 and other graft‐type sulfonated membranes 23 …”
Section: Resultssupporting
confidence: 76%
“…On the basic of the relatively small size Ps probe, the experimentally measured o‐ Ps lifetime can be utilized to investigate the free‐volume hole features in polymers. So far, only several studies have utilized the PALS to probe the microstructures of alternative PEMs, 8,16–18 whereas most of the attention is focused on the commercial Nafion membranes and their composites 19–22 . Moreover, there is only one work on the graft‐type PEMs, 23 leading to a very limited understanding of the subnano holes and their relation to the fuel cell performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[44][45][46] Thus, gas permeation in polymer is a very complex phenomenon, and there is rarely a simple linear relation between the gas permeability and a given parameter. [44][45][46]90 We found that there is no linear relation between the free volumes and the gas permeability for the PEI/RGO composite lms. Nevertheless, the PALS results strongly suggest that the decrease in free volume size has made a signicant contribution to the excellent gas barrier property of the PEI/RGO composite lms.…”
Section: Permeation Of Gas Molecules Within Rgo/pei Composite Lms In...mentioning
confidence: 74%